Faecal microbiota transplantation: Where did it start? What have studies taught us? Where is it going?. (9th May 2017) - Chanyi, Ryan M; Craven, Laura; Harvey, Brandon; Reid, Gregor; Silverman, Michael J; Burton, Jeremy P
The composition and activity of microorganisms in the gut, the microbiome, is emerging as an important factor to consider with regard to the treatment of many diseases. Dysbiosis of the normal community has been implicated in inflammatory bowel disease, Crohn's disease, diabetes and, most notoriously, Clostridium difficile infection. In Canada, the leading treatment strategy for recalcitrant C. difficile infection is to receive faecal material which by nature is filled with microorganisms and their metabolites, from a healthy individual, known as a faecal microbiota transplantation. This influx of bacteria into the gut helps to restore the microbiota to a healthy state, preventing C. difficile from causing further disease. Much of what is known with respect to the microbiota and faecal microbiota transplantation comes from animal studies simulating the human disease. Although these models allow researchers to perform studies that would be difficult in humans, they do not always recapitulate the human microbiome. This makes the translation of these results to humans somewhat questionable. The purpose of this review is to analyse these animal models and discuss the advantages and the disadvantages of them in relation to human translation. By understanding some of the limitation of animal models, we will be better able to design and perform experiments of most relevance to human applications.